Penyuluhan Hukum Tentang Tindak Pidana Kekerasan Dalam Rumah Tangga Dan Penanganannya Di Desa Rumberu, Kecamatan Inamosol Kabupaten Seram Bagian Barat - Judy Marria Saimima; Carolina Tuhumury; Akhmad Iqbal Jihad Masuku (Faculty of Law, Universitas Pattimura, 2021)
Introduction: In the current development of society, acts of domestic violence in the form of physical, psychological, sexual and neglect in domestic life actually occur, so that in order to eliminate domestic violence, an effective handling or law enforcement action is needed.Purposes of Devotion: To provide a legal understanding of criminal acts of domestic violence and its handling in Rumberu Village, Inamosol District, West Seram Regency. Method of Devotion: Conducted by the lecture method by each presenter, after the presentation of the material, the participants are given the opportunity to convey the legal problems experienced, then answered by the presenter in accordance with the substance of the material presented.Results of the Devotion: The public can understand that all forms of violence, especially domestic violence, are violations of human rights and crimes against human dignity as well as forms of discrimination that must be eliminated. Legal understanding of PKDRT helps the community, especially in RT.004/Kilo 9 Rumberu Village, Inamosol District, West Seram Regency to realize their rights.